THE RELATIONSHIP BETWEEN MATERNAL HEIGHT DURINGPREGNANCY AND THE INCIDENCE OF STUNTING IN TODDLERS AT THERONGKOP COMMUNITY HEALTH CENTER, GUNUNG KIDUL IN 2025 - Eka Oktavia; Lara Audi Setyawati (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Stunting is a global nutrition problem. World Health Organization Data shows that as many as 22% of toddlers experience stunting, which can affect children's cognitive development  in  the  future.  The  incidence  of  stunting  in  Indonesia  remains  high  in 2024  according  to  the  SSGI  (Indonesian  Nutritional  Status  Survey).  The  national stunting  prevalence  is  19.8%.  While  the  target  for  2025  is  18.8%,  the  Indonesian government  must  continue  to  strive  to  reduce  stunting  cases  to  reach  the  target  of 18.8%.  The  government  program  to  provide  free  nutritious  food  for  pregnant  and breastfeeding mothers and children aged 2-5 years has been implemented as an effort to reduce stunting cases, but the issue of maternal height also affects the incidence of stunting. Women of childbearing age who are under 150 cm tall are at high risk of giving birth to stunted babies. Yogyakarta is one of the developed cities in Indonesia known as a city of education, but still has quite high cases of stunting in toddlers in one of the districts in Gunung Kidul. Although maternal height has been identified as a  risk  factor  for  stunting,  local  evidence  shows  that  areas  with  a  higher  burden  of stunting incidence, such as in the Rongkop Community Health Center working area, have stunting incidences of 60 respondents out of a total of 148 toddlers in 2025. The purpose of this study was to determine the relationship between maternal height and the  incidence  of  stunting  in  toddlers  at  the  Rongkop  Community  Health  Center, Gunung Kidul in 2025. This study used a quantitative method with a cross-sectional study design, with a total sampling of 148 respondents. Data were analyzed using the chi-square test. The  results  of  the  study  is  that  there  are  148  respondents  who  are  pregnant  with reproductive  age  characteristics  of  20-35  years  85,1%,  with  employment  as  a housewife  62,2%  and  the  highest  level  of  education  is  senior  high  school  45,9%. Mother's height data short <150 cm is 14,2% and all of them gave birth to incidence of  stunting  toddlers.  The  results  of  the  Chi-Square  analysis  showed  a  significant relationship (0.001 <0.05). Conclusion  There  is  a  relationship  between  maternal  height  and  the  incidence  of stunting in toddlers at Rongkop Community Health Center, Gunung Kidul Regency in 2025.